2012
DOI: 10.1007/s10899-012-9329-6
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Switching and Non-switching Slot Machine Player Behaviour

Abstract: Learning theory predicts that, given the repeated choice to bet between two concurrently available slot machines, gamblers will learn to bet more money on the machine with higher expected return (payback percentage) or higher win probability per spin (volatility). The purpose of this study was to investigate whether this occurs when the two machines vary orthogonally on payback percentage and volatility. The sample comprised 52 first year psychology students (mean age = 20.3 years, 20 females, 32 males) who ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 45 publications
4
18
1
Order By: Relevance
“…Dixon et al ( 2006 ) found that gamblers prefer games with more frequent but smaller wins to games with less frequent and big wins. In line with these findings, Coates and Blaszczynski ( 2012 ) found that individuals prefer games with more frequent wins and higher payback percentages. These findings suggest that players will prefer games with more frequent wins and higher payback percentages when they are able to discriminate and choose between games with different reward characteristics.…”
Section: Introductionmentioning
confidence: 62%
See 3 more Smart Citations
“…Dixon et al ( 2006 ) found that gamblers prefer games with more frequent but smaller wins to games with less frequent and big wins. In line with these findings, Coates and Blaszczynski ( 2012 ) found that individuals prefer games with more frequent wins and higher payback percentages. These findings suggest that players will prefer games with more frequent wins and higher payback percentages when they are able to discriminate and choose between games with different reward characteristics.…”
Section: Introductionmentioning
confidence: 62%
“…These results are also consistent with previous laboratory findings. Coates and Blaszczynski ( 2012 ) found that participants who were able to discriminate and choose between games with different payback percentages developed a preference for games with a higher payback percentage. In contrast, Haw ( 2007 ) found a significant relationship between gambling machine choice and payback percentage only among participants who switched gambling machines during a laboratory session.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One example of this is the matching law (Herrnstein, 1974) and its generalization (Baum, 1974), which attempts to describe how organisms distribute responding to multiple concurrent ratio or interval schedules. There is a literature on response allocation in concurrent slot machines, but findings in this area have been mixed; a number of studies (Coates & Blaszczynski, 2014;Daly et al, 2014;Dixon, Fugelsang, MacLaren, & Harrigan, 2013;Dixon, MacLin, & Daugherty, 2006;Dymond, McCann, Griffiths, Cox, & Crocker, 2012;Zlomke & Dixon, 2006) found evidence consistent with matching, but there is also evidence gamblers undermatch, showing greater (or in some cases, total) equivalence between machines that diverge either in rate of return to player or rate of reinforcement on a ratio schedule (Coates & Blaszczynski, 2013;Daly et al, 2014;Lucas & Singh, 2012;Weatherly, Thompson, Hodny, Meier, & Dixon, 2009). In addition, matching is highly susceptible to being overridden by contextual cues (Nastally, Dixon, & Jackson, 2010;Zlomke & Dixon, 2006) although this appears to weaken with extended exposure to the contingencies of a machine (Hoon & Dymond, 2013).…”
Section: Behavioural Mechanismsmentioning
confidence: 99%